Analisis Kemampuan Pemecahan Masalah Matematis dalam Menyelesaikan Soal Segi Empat - Meilina, Agnes; Dzakwan, Ibnu; Br. Marbun, Nur Azizah; Ramadhani, Ramadhani (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2025)
This research is based on low, medium and high problem solving abilities to solve contextual problems. Researchers used a qualitative descriptive approach to analyze the problem solving abilities of SMP Negeri 34 Medan class VIII using rectangular material. The next data collection technique is interviews. The test was carried out on 29 students, where three people were selected who had high (S1), medium (S2), and low (S3) problem solving abilities. Based on the results of tests and interviews, students in the high category have four areas of mathematical problem solving ability: the ability to understand problems, the ability to formulate problem solving plans, the ability to solve problems, and recheck the answers they get.  This shows that the indicators can be met. Students show that in the medium category they are able to fulfill three indicators of mathematical problem solving ability: the ability to understand a problem, the ability to formulate a problem solving plan, and the ability to carry out problem solving. . On the other hand, students who are in the low category show that they are only able to fulfill two indicators, namely understanding the problem and planning a solution to the problem.